2021
DOI: 10.48550/arxiv.2112.07223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapidly enhanced spin polarization injection in an optically pumped spin ratchet

Abstract: Rapid injection of spin polarization into an ensemble of nuclear spins is a problem of broad interest, spanning dynamic nuclear polarization (DNP) to quantum information science. We report on a strategy to boost the spin injection rate by exploiting electrons that can be rapidly polarized via high-power optical pumping. We demonstrate this in a model system of Nitrogen Vacancy center electrons injecting polarization into a bath of 13 C nuclei in diamond. We innovate an apparatus with thirty lasers to deliver >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Sensor properties for AC magnetometry: focusing on sensitivity, bandwidth, spectral resolution, precision, and operating field. We note that while our experiments were carried out on a diamond crystal that was uniformly illuminated, we estimate a penetration depth <0.15mm [56,74]. Sensitivity refers to the smallest field that can be reproducibly measured over the bias magnetic field.…”
Section: Comparison Between Nv and 13 C Magnetometersmentioning
confidence: 98%
See 2 more Smart Citations
“…Sensor properties for AC magnetometry: focusing on sensitivity, bandwidth, spectral resolution, precision, and operating field. We note that while our experiments were carried out on a diamond crystal that was uniformly illuminated, we estimate a penetration depth <0.15mm [56,74]. Sensitivity refers to the smallest field that can be reproducibly measured over the bias magnetic field.…”
Section: Comparison Between Nv and 13 C Magnetometersmentioning
confidence: 98%
“…Similarly, optically hyperpolarized sensors present advantages because majority of the sensor volume can be illuminated by the impinging lasers, because there are no geometrical constraints from requirements of collection optics. In our experiments, we employed an array of low-cost laser diode sources [56] for hyperpolarization that illuminates the sample almost isotropically. This allows recruiting a larger volume of spins for sensing with a low cost overhead [56].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9]. As an example, in the experiment [29], it was demonstrated that by cooling the diamond sample with water and N 2 gas, the temperature raise can be managed within 30 K for the laser power up to 24 W. If this cooling is still efficient for much larger laser power, we expect the temperature rise of 125 K for the laser power 100 W, and the drift of the frequency by 2π × 9.25 MHz. This kind of heating is still accepted and the frequency drift can be counteracted by tunning the Zeeman shift induced by a proper magnetic field.…”
Section: Appendix F: Counteracting Optical Heating Of Diamondmentioning
confidence: 99%
“…Such electron induced nuclear relaxation is an important consideration for applications in quantum registers, memories, and sensors constructed out of nuclear spins [9][10][11], and is therefore important to quantify. It also plays a key role in determining rates of polarization transfer in DNP [12][13][14]. However, probing such relaxation influences, particularly in a spatially defined manner, is challenging.…”
mentioning
confidence: 99%